Pulmonary Embolism and Intracardiac Type A Thrombus with an Unexpected Outcome - João Português; Lucy Calvo; Margarida Oliveira; Vítor Hugo Pereira; Joana Guardado; Mário Rui Lourenço; Olga Azevedo; Francisco Ferreira; Filipa Canário-Almeida; António Lourenço (Case Reports in Cardiology)
Detection of right heart thrombi (RHT) in the context of pulmonary thromboembolism (PE) is uncommon (4–18%) and increases the risk of mortality beyond the presence of PE alone. Type A thrombi are serpiginous and highly mobile and are thought to be originated from large veins and captured in-transit within the right heart. Optimal management of RHT is still uncertain. A 79-year-old woman, with a history of recent total hysterectomy with adnexectomy and a Wells procedure, presented to the emergency department following an episode of syncope. Computed tomography revealed bilateral PE and the presence of a right atrial thrombus. Transthoracic echocardiography demonstrated a free-floating type A thrombus in the right atrium, protruding into the right ventricle, and signs of pulmonary hypertension and right ventricle dysfunction. Considering the recent surgery and clinical stability, treatment with heparin alone was decided. Subsequent clinical improvement was observed and echocardiographic follow-up revealed complete thrombus dissolution and complete recovery of right ventricle function. Most authors recommend treatment of PE with RHT with thrombolysis or embolectomy followed by anticoagulation, although evidence is scarce. Individual risk of hemorrhage and operatory-related mortality should be taken into account when defining the treatment strategy especially when benefit is not firmly established.